PERSEPSI KONSUMEN TERHADAP PERSAINGAN ANTAR MEREK MELALUI IKLAN (STUDI KASUS PERSAINGAN ANTAR PRODUK DETERJEN RINSO DAN SO KLIN) - Lusia Nargis (JURNAL KOMPETITIF, 2012)
This research aims to know about consumer perception of detergent brand competition in Indonesia, focused in Rinso and So Klin by advertising or nonadvertising. The result of this research indicated that 58 percent of the respondent claimed brand competition between Rinso and So Klin was the most dominant, and 25 percent of the respondent claimed that Rinso was competing with Surf, whereas Surf and Rinso were one product which were made as fighting brand to attack other brand competitors. Only 11 percent of them perceived the competition between Surf dan So Klin. The result of contingency correlation is 0,54 and the level of confidence is 0,01. It indicated  that there was a correlation between advertising and consumer perception in detergent brand competition.Key word : consumer perception, merk, competition, fighting brand, brand competition